Examining the Impact of Leadership Approach and Principal's Drive on Educator Productivity: Investigation at a Senior High School in Medan - Elly Romy (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research aims to investigate the impact of school principal leadership styles and motivation on teacher performance in a senior high school in Medan. Employing a quantitative research approach, the study focuses on a population comprising all teachers and staff at the selected school, with a final sample size of 47 individuals. The findings reveal several conclusions regarding the effects of leadership and motivation on teacher performance. Individually, the results indicate that leadership significantly influences teacher performance, with the calculated t value for leadership exceeding the critical t value. Likewise, motivation shows a significant effect on teacher performance, as the motivation variable's t value is greater than the critical value, with a significance level of less than 0.05. This suggests that as motivation increases, teacher performance improves correspondingly. Collectively, both leadership and motivation demonstrate a significant impact on teacher performance, evidenced by the calculated F value being greater than the table F value. The coefficient of determination indicates a noteworthy relationship between leadership, motivation, and teacher performance. The implications of this research emphasize the necessity for school principals to adopt effective leadership styles and promote motivation among teachers to enhance their performance. Future studies may explore additional factors influencing teacher performance and incorporate qualitative methods to gain deeper insights into teacher experiences.